Pengembangan Media Pembelajaran Game Berbasis Android pada Materi Sistem Komputer Kelas X SMAN 1 Sungai Raya Kepulauan - Arya Karza; Ferry Andriyanto; Apra Andika; Indra Cahyadi; Dayang Guan Lestari (PT. PENERBIT TIGA MUTIARA, 2024)
The objective of this research is to provide engaging and tailored learning materials that cater to the needs of students, facilitating comprehension and playing a vital part in achieving academic achievement. This study employs the Research and Development (R&D) methodology. Through the utilization of research and development (R&D), the primary focus of investigation can be directed towards the creation, advancement, and assessment of learning media in terms of design and viability. The end result is an Android game that serves as a learning tool for computer system topics. The assessment findings indicate that the storyboard design has achieved a validity score of 4.91 out of 5, placing it in the “Very Good” category. The score was derived from the evaluation of two design professionals. The initial design expert assigned a validity score of 4.88, while the second design expert assigned a validity score of 4.94 on a 5-point scale. These scores indicate that the research results fall into the “Very Good” category. According to the assessment conducted by linguists, the language employed in creating the tale has been given a validity score of 4.73 out of 5, placing it in the “Very Good” category. The score was derived from two linguists. The initial linguist assigned a validity score of 4.5, while the second linguist assigned a validity score of 4.7 on a 5-point scale. These scores placed the results of the study in the “Very Good” category. The study has reached its conclusion. The development step use the RPG Maker MV program. The development results include the creation of various maps such as the devil's palace map (for the purpose of kidnapping the royal princess), prologues 1 and 2, the map inside the king's palace, the map outside the king's palace, the village map, the library map, the sword shop map, the armor shop map, the forest map, the bridge map, the desert map, the cave map, the magma map, the devil's palace outer map, the devil's palace inside map, the king's palace page map, and the epilogue.